2022
DOI: 10.3390/microorganisms10020318
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Probiotic Modulation of the Intestinal Microbiota and 2′Fucosyllactose Consumption in Fecal Cultures from Infants at Two Months of Age

Abstract: 2′-fucosyllactose (2′FL) is one of the most abundant oligosaccharides in human milk, with benefits on neonatal health. Previous results point to the inability of the fecal microbiota from some infants to ferment 2′FL. We evaluated a probiotic formulation, including the strains Lactobacillus helveticus Rosell®-52 (R0052), Bifidobacterium longum subsp. infantis Rosell®-33 (R0033), and Bifidobacterium bifidum Rosell®-71 (R0071), individually or in an 80:10:10 combination on the microbiota and 2′FL degradation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The increase in this metabolite in FF newborns is driven by the catabolic pathways of amino acids, such as isoleucine, which is found in high-protein infant formulae. Moreover, recent studies of fecal cultures of healthy 2-month-old neonates revealed the interrelation of succinate compounds with the establishment of commensal Enterobacteriaceae communities in the FF infant gut [ 65 ]. Apart from the feeding mode, the concentrations of methyl-succinate has been shown to significantly depend on the age of the infant [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in this metabolite in FF newborns is driven by the catabolic pathways of amino acids, such as isoleucine, which is found in high-protein infant formulae. Moreover, recent studies of fecal cultures of healthy 2-month-old neonates revealed the interrelation of succinate compounds with the establishment of commensal Enterobacteriaceae communities in the FF infant gut [ 65 ]. Apart from the feeding mode, the concentrations of methyl-succinate has been shown to significantly depend on the age of the infant [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with HMOs may therefore potentially increase bifidobacteria and bring microbiota composition closer to that of breastfed infants. In RCT, the microbiota composition in a 2’-FL formula (1 g/L) group was only just significantly different at 2 months and just not at 3 months of age, bringing the microbiota composition somehow closer to that of breastfed infants 159 .…”
Section: Hmos and Anthropometrymentioning
confidence: 91%
“… Infants receiving HMO containing formula had significantly fewer parental reports of parent-reported morbidities related to lower respiratory tract infections as well as antipyretic and antibiotic. Alliet et al 159 2022 2’FL + L. Reuteri DSM 17,938 Belgium, Italy 2017–2019 Healthy, term (37–42 weeks gestation) infants aged≤14 days at enrollment with a birth weight between 2500 and 4500 g Standard bovine milk-based whey predominant formula with an energy density of 670 kcal/L containing 75 g/L lactose, 34 g/L fat, 14 g/L protein (60:40 whey: casein ratio), and L. reuteri DSM 17,938 + 1 g/L 2’FL which i Standard bovine milk-based whey predominant formula with an energy density of 670 kcal/L containing 75 g/L lactose, 34 g/L fat, 14 g/L protein (60:40 whey:casein ratio), and L. reuteri DSM 17,938 Breastfed infants 180 days Weight gain in HMO formula was non-inferior to a non-HMO supplemented formula. Anthropometric Z-scores, parent-reported stooling characteristics, gastrointestinal symptoms and associated behaviors, and AEs were comparable between formula groups.…”
Section: Hmos and Anthropometrymentioning
confidence: 99%
“…Batch cultivation and the CoMiniGut model (University of Copenhagen, Copenhagen, Denmark) have been used to evaluate the effects of 3-FL on the infant microbiota [ 30 , 31 ]. The composition of the infant microbiota varies widely between infants who donate the faecal inoculum, introducing variability in infant simulations and affecting the efficiency of HMO utilisation [ 25 , 26 , 27 , 28 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%